Sistem Informasi Peramalan Penjualan Produk Dengan Menggunakan Metode Fuzzy Time Series Berbasis Web (Study Kasus: CV. Surya Kencana Food) - Yusuf, Lutfi; Mashuri, Chamdan; Zein Vitadiar, Tanhella (Inovate, 2021)
Sales forecasting is a program to forecast future sales based on historical data that aims to reduce the excess in producing goods. This research was conducted at the company CV. Surya Kencana Food, Jln. Brigadier General Kretarto No 189 Jombang 61413, Jombang District, Jombang Regency. In selling goods, the company has difficulty estimating how many sales for the next month, resulting in the company producing goods in excess that are not in accordance with market demand, which results in companies experiencing losses. This study aims to build a computerized system that can help the process of selling goods that can help companies in selling goods in the next month based on historical data. In action research. This research method which consists of four stages consisting of: planning, action, observation and reflection, with the calculation process using the Fuzzt Time Series (FTS) method that uses calculations based on historical data. The results of this study are in the form of a decision support system which is expected to help the company in predicting (predicting) sales of Gerry products in the following month. In the calculation process, forecasting accuracy is done using MAPE to test how accurate the forecasting is. Results of forecasting in December 2019, namely: 13817 with a MAPE value of 9.46%. Keywords: Product Sales, Forecasting, Information System, Fuzzy Time Series